Proteomic analysis of human liver cell line incubated with s-enantiomer of warfarin - Tay, Jacqueline Mei Shi. (2009)
Warfarin acts as a specific inhibitor of vitamin K epoxide reductase, with S-enantiomer being more active than R-enantiomer. It is clinically used as oral anti-coagulant to effectively treat patients with pulmonary embolism. To achieve an optimal therapeutic response with minimum side effects, quantitative protein profiling was established to investigate on protein with differential expression levels in hepatocellular carcinoma (HepG2) cells incubated with individual enantiomers of warfarin using the iTRAQ-coupled two-dimensional LC-MS/MS method. Unique proteins identified were categorized into four different functional groups comprising of metabolic enzymes, signal transduction molecules, transporters and thiol-disulfide related proteins. Results analyzed revealed an up-regulation of metabolic enzymes with protein level higher in S- than R-enantiomer incubated cells. Down-regulation of signal transduction and thiol-disulfide related proteins were also observed displaying a lower protein level in HepG2 cells incubated with S-enantiomer than with R-enantiomer. L-lactate dehydrogenase A chain, 14-3-3 protein sigma and S100-A11 were believed to have a subsidiary influence on the anti-coagulating process by affecting the collagen level in the warfarin-treated HepG2 cells. Thiol-disulfide related proteins detected were discovered to act directly on vitamin K cycle related enzymes or co-enzymes. These proteins analyzed were helpful in providing a reference for manufacturing and commercializing of new racemic drug in the market. Further analysis of protein 14-3-3 and thioredoxin disclosed an association of their functions to cell apoptosis regulation, serving as vital and useful targets for reducing clinical side effects like hemorrhage in warfarin treated-cells.